The role of dynamic process models for the detection of safe operating regions of process systems - Varga, Tamás; Baradits, György; Abonyi, János (Acta Agraria Kaposváriensis, 2010)
Determining safe regions of operations is important at the design, control and optimization of process systems. E.g. process alarms and safety systems should be designed based on such knowledge. In classical control systems these regions are represented as independent values (constraints) on process variables. This representation is does not consider the interaction of the process variables, and moreover it gives a static view of the process. The paper reviews the importance of the representation of the safe operating regions from an industrial application point of view and the recent tools developed for model-based alarm management. The importance of the application of dynamical analysis of process models is highlighted. A detailed case study is given where this dynamical approach has been applied to determine boundaries of operating regions of a catalytic tube reactor.